A Comparative Study of Intelligence and Academic Achievement of Higher Secondary School Students in Relation to Their Gender, Stream, and Socio-Economic Status - Kalhotra, Satish Kumar (ATIKAN, 2014)
ABSTRACT: With the advancement of knowledge, the world is becoming more and more competitive. Quality of performance has become the key factor for an individual achievement. The present study was carried out to compare intelligence and academic achievement in relation to studentsâ gender, stream, and socio-economic status. Total 200 boys and girls from Science and Humanities streams were taken as the sample of the study. Investigator used M.C. Joshiâs intelligence test (1956) and socio-economic status scale by S.D. Kapoor & H.C. Kocher (1997-1998) for collecting the data. T-Test and product moment method was used to find the results. The study reveals that girls on an average have high intelligence as compared to boys. On an average the male and female students have similar academic achievement. On an average Science studentâs high intelligence than the Humanities students. The correlation between intelligence and academic achievement have come out to be positive and significantly. This shows that higher the intelligence will be higher the academic achievement. The correlations between intelligence and socio-economic status have come out to be non-significant. This means that intelligence and socio-economic status are not correlated with each other.KEY WORD: Intelligence, academic achievement, socio-economic status, gender, Science and Humanities streams, and high intelligence.IKHTISAR: âStudi Perbandingan tentang Kecerdasan dan Prestasi Akademik para Siswa Sekolah Menengah Atas dalam Kaitannya dengan Gender, Jurusan, dan Status Sosial-Ekonomi Merekaâ. Dengan kemajuan pengetahuan, dunia menjadi semakin kompetitif. Kualitas kinerja menjadi faktor kunci untuk keberhasilan individu. Penelitian ini dilakukan untuk membandingkan kecerdasan dan prestasi akademik dalam kaitannya dengan gender, jurusan, dan status sosial-ekonomi para siswa. Sebanyak 200 siswa laki-laki dan perempuan dari jurusan Sains dan Humaniora diambil sebagai sampel penelitian. Peneliti menggunakan uji kecerdasan dari M.C. Joshi (1956) dan skala status sosial-ekonomi oleh S.D. Kapoor & H.C. Kocher (1997-1998) untuk mengumpulkan data. T-Test dan metode hasil seketika digunakan untuk mendapatkan hasil penelitian. Penelitian ini mengungkapkan bahwa para siswa perempuan, rata-rata memiliki kecerdasan yang tinggi dibandingkan dengan para siswa laki-laki. Mengenai rata-rata siswa laki-laki dan perempuan memiliki prestasi akademik yang sama. Rata-rata kecerdasan siswa pada ilmu Sains lebih tinggi daripada siswa ilmu Humaniora. Korelasi antara kecerdasan dan prestasi akademik menjadi positif dan signifikan. Hal ini menunjukkan bahwa semakin tinggi kecerdasan akan menjadi lebih tinggi pula prestasi akademik. Korelasi antara kecerdasan dan status sosial-ekonomi menjadi tidak signifikan. Ini berarti bahwa kecerdasan dan status sosial-ekonomi tidak berkorelasi satu sama lain.KATA KUNCI: Kecerdasan, prestasi akademik, status sosial-ekonomi, jenis kelamin, jurusan Sains dan Humaniora, serta kecerdasan yang tinggi.About the Author: Dr. Satish Kumar Kalhotra is an Assistant Professor at the Maulana Azad National Urdu University, Hyderabad, India. For academic purposes, the author can be contacted via his e-mail address at: drsatishkumarkalhotra@gmail.comHow to cite this article? Kalhotra, Satish Kumar. (2014). âA Comparative Study of Intelligence and Academic Achievement of Higher Secondary School Students in Relation to Their Gender, Stream, and Socio-Economic Statusâ in ATIKAN: Jurnal Kajian Pendidikan, Vol. 4(1) June, pp.35-46. Bandung, Indonesia: Minda Masagi Press and UNSUR Cianjur, ISSN 2088-1290.Chronicle of the article: Accepted (March 30, 2014); Revised (May 15, 2014); and Published (June 29, 2014).